Proteolytic specificity of chicken cathepsin L on bovine β-casein. Issue 2 (April 1988) - Dufour, Eric; Ribadeau-Dumas, Bruno
Abstract : The proteolytic specificity of chicken cathepsin L was studied using bovine β-casein as substrate. The peptide mixtures obtained after various times of hydrolysis were separated by RP-HPLC and ten peptides were identified. Chicken cathepsin L accepts proline residues in all positions except P1 ′ . Looking at the amino acid residues on the amino side of the scissile bond we found three times the Tyr-Pro pair at P1 ′ –P2 ′ positions and that the S1 ′ subsite can interact with modified amino acids such as phosphoserine.